The monkey in the mirror and other tales of central bank forward guidance - Remolona, Eli M. (Philippine Review of Economics, 2019)
The literature advises central banks to provide forward guidance so as to make themselves predictable to markets. If possible, forward guidance should be Odyssean, in which the central bank commits itself to a clear course of action in the future. Central banks, however, often find themselves defying the theory by offering forward guidance that is rather reticent. Sometimes, the central bank may even deliberately surprise the markets. These departures from theory make sense in markets that behave as Keynesian beauty contests, in which some signals carry inordinate weight and thus lead markets astray. A degree of reticence compels market participants to do their own analysis and offer an independent view that can be useful to central banks. Otherwise, the central bank would find itself merely watching itself in the mirror. In some circumstances, the market may get stuck in a deleterious equilibrium, one born out of a false but well-told narrative. This may call for a “shock and awe” strategy, in which the central bank acts to surprise the market to force a rethinking of the narrative.